Serum superoxide dismutase (SOD), malondialdehyde (MDA) ,IL-6, IL-8, TNF-α, serum immune markers after Allogeneic Blood Transfusion in Patients with Gastrointestinal Bleeding: serum SOD and MDA , IL-6, IL-8, TNF-α, - Zaikai Lin, Zaikai Lin (Journal of Medical Biochemistry, 2025)
Aim:this article was to analyze the changes serum superoxide dismutase (SOD), malondialdehyde (MDA) ,IL-6, IL-8, TNF-α, serum immune markers indicators in the serum of patients with gastrointestinal hemorrhage and the impact on the immune function of the body after allogeneic blood transfusion (ABT) during surgery. Methods:80 patients who diagnosed with gastrointestinal bleeding (GIB) and required surgical treatment were enrolled. 40 patients in the experimental group (EG) were given intravenous infusion of 2 4 U of red blood cells during the surgery, and 40 patients in the control group (CG) were not treated with allogeneic blood transfusion during the surgery. The cubital venous blood of patients was drawn before the ABT and 1 day after the ABT to check the changes in the T cell subsets, natural killer cells (NKC), immune globulin, serum inflammatory factors, count of platelets, oxidative stress indicators, and hemostasis time. Results: 1 day after ABT, NKC, CD3+, CD4+, and CD4+/CD8+ in the EG were much lower as against prior to ABT; the immunoglobulin G (IgG) in the EG was lower (P< 0.05); the changes of IgA, and IgM in patients were not obvious (P> 0.05); and IL-6, IL-8, and tumor necrosis factor α (TNF)-α were greatly increased (P< 0.05). The counts of platelet the two groups were reduced prior to ABT and one day after ABT, but the changes were not obvious (P> 0.05). After ABT, the increase in serum superoxide dismutase (SOD) and the decrease in malondialdehyde (MDA) in the EG were greater as against the CG; The hemostasis time (the disappearance of coffee-like substances or the disappearance of blood in the excrement) and the time for occult blood to become negative in the EG were shorter as against the CG (all P< 0.05). Conclusion: It suggested that the ABT was effective in the treatment of GIB, but it had a visible inhibitory effect on immune function. In addition, the amount of ABT had no visible effect on the platelet function of patients within a certain range, and the oxidative stress indicators of patients changed obviously after ABT, indicating that it can inhibit the peroxide response of patients with GIB.